1999
DOI: 10.1021/cm990117q
|View full text |Cite
|
Sign up to set email alerts
|

Valence Electronic Structure of π-Conjugated Materials:  Simulation of the Ultraviolet Photoelectron Spectra with Semiempirical Hartree−Fock Approaches

Abstract: A detailed understanding of the electronic structure of π-conjugated materials can be reached by means of two widely available semiempirical quantum-chemical methods: Austin model 1 (AM1) and intermediate neglect of differential overlap (INDO). This is illustrated by calculating the ultraviolet photoelectron spectra (UPS) of π-conjugated oligomers and polymers and comparing the theoretical data to experimental spectra. The approach is applied here to a series of compounds with varying molecular topology and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 45 publications
5
49
1
Order By: Relevance
“…The disagreement between the HF eigenvalues and the UPS data is unexpected since it has been shown that such an HF theoretical scheme is successful in simulating the electronic structure of other conjugated oligomers. 25 As shown in Fig. 4, there is a one-to-one correspondence between the spectral features recorded in the gas and solid phase.…”
Section: Theoryõexperiments Comparisonmentioning
confidence: 69%
See 2 more Smart Citations
“…The disagreement between the HF eigenvalues and the UPS data is unexpected since it has been shown that such an HF theoretical scheme is successful in simulating the electronic structure of other conjugated oligomers. 25 As shown in Fig. 4, there is a one-to-one correspondence between the spectral features recorded in the gas and solid phase.…”
Section: Theoryõexperiments Comparisonmentioning
confidence: 69%
“…The approach has been extensively described in connection with the studies of conjugated molecules, where the DOVS curves were obtained by either ab initio or semiempirical HF methods. 25 Using Koopmans' approach, the peaks in the UPS spectra are associated to eigenenergies calculated for the electronic levels in the neutral molecule. The following steps were taken to facilitate comparison of the theoretical results with the experimental spectra.…”
Section: Theoretical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The computed densities of states for the occupied and unoccupied levels were convolved with a Gaussian function and rigidly shifted on the energy scale (by -2.6 and -0.5 eV to match the position of the first peak in each case), in order to simulate the solid-state UPS and IPES spectra, respectively. Extensive studies on a variety of systems have shown that such a simulation procedure, which effectively allows one to include solid-state polarization effects, reproduces experimental spectra very well [23,24].…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…25 A detailed description can be found elsewhere. 26,27 As discussed above, the presence of TDAE at the ITO surface is revealed by a photoemission signal corresponding to -orbitals of the molecules. Meanwhile, the low binding energy feature at 2.2 eV, associated to the highest occupied molecular orbital of TDAE, is absent in the spectrum of modified ITO.…”
mentioning
confidence: 88%